(untitled) (Scientific journal of the Fergana State University, 2023)
This article outlines the issues of using smart technologies and training future teachers with their help, the need to introduce progressive approaches and methods into the educational process, the emergence of the concept of “smart”, the implementation of the smart educational process through information technology and pedagogical aspects of technologies, software and tools, achievements, advantages of smart technologies and much more.